(untitled) (Vietnam Journal of Community Medicine, 2026)
Objects: To describe the knowledge and practices related to infection prevention among patients undergoing continuous ambulatory peritoneal dialysis at the Nephrology - Urology and Dialysis Center, Bach Mai Hospital, in 2025. Methods: A cross-sectional descriptive study conducted on 121 patients undergoing continuous ambulatory peritoneal dialysis. Results: 74.4% of patients had high knowledge scores; 19.8% had moderate knowledge levels, and only 5.8% had low knowledge. The group of questions related to peritonitis had the lowest mean error rate (5.5%). Questions concerning catheter exit-site infection had a mean error rate of 9.1%. The area with the greatest knowledge gap was the management of complications at home, with the highest mean error rate (9.5%). Regarding practice, most patients met the required performance standards, accounting for 76.9%. However, 23.1% did not meet the standards. Although over 50% of participants performed most procedural steps correctly, several steps related to hand hygiene and disinfection showed lower accuracy-particularly the 2 and 3 rounds of alcohol-based hand rub. Additionally, steps such as timing the procedure, observing the effluent, and documenting information after weighing the dialysis bag were not consistently completed Conclusion: Most patients demonstrated a high level of knowledge regarding infection prevention, reflecting the initial effectiveness of counseling, guidance, and health education at the treatment facility. In terms of practice, the majority performed the required technical steps in continuous ambulatory peritoneal dialysis adequately. However, some limitations still exist, therefore, enhanced communication, health education, and practical training are needed to improve knowledge, practices, and reduce infectious complications.